Human Factors in the operating room - the surgeons view - Kurmann, Anita; Tschan, Franziska; Semmer, Norbert K; Seelandt, Julia; Candinas, Daniel; Beldi, Guido (My University, 2012)
The quality of surgical performance depends not only on the technical skills of the surgical team, but also on non-technical skills. Identification and improvement of such non-technical skills is an important aim to improve overall surgical outcomes. Non technical skills primarily include three factors. The first factor is efficient communication among a multidisciplinary team. This requires strong leadership and coor- dination of role-related tasks for the surgical team members. The second factor is coping with distractors in the operating room. Distractors may impact team performance and must be identified and reduced to ensure maximum concentration in the most of unavoidable distractions. The third factor is the impact of stress and fatigue of the surgical team. Potential methods of addressing these topics include training, procedural support for human factors requirements, and specified phases for information reflection as well as for mental recovery